The effects of financial knowledge, socialisation, attitude and skill on Malaysian SMEs’ performance - Abdul Razak, Dzuljastri; Amin, Hanudin (Universiti Malaysia Pahang (UM), 2020)
Though considered trivial, small and medium enterprises (SMEs) were one of the contributing factors for Malaysia economy growth. Besides providing employment, SMEs also provide an improved integration to ensure other businesses survive in the long run. Thus, the present study examined the contributing factors to explain SMEs' performance, be it high or negative. Drawing upon the financial literacy theory, this study proposed a model of factors to examine the effects of financial knowledge, socialisation, attitude and skill on the performance of SMEs industry in Malaysia. The model was examined using owners of the SMEs drawn from 413 respondents collected in West Malaysia. Our results suggested that the said indicators were instrumental in determining the performance, and attitude was also essential as a mediator as discovered in our PLS analyses. In practice, however, this study jacked up a new understanding of why SMEs' performance is of importance, and the survey approach in measuring the performance is nothing but important. Our findings provide an insight for owners of SMEs to manage their businesses, where financial socialization, financial attitude and financial skill are brought into play